Pengaruh Pendidikan Kewarganegaraan Terhadap Pembentukan Karakter Siswa - Yanita Devaraswari; Citra Aulia Restu; Shakila Putri; Hanisah Putri; Ersa Deltia (Journal of Creative Student Research, 2024)
Citizenship education plays an important role in shaping the character of students by teaching them the rights and duties of citizenship, the principles of democracy, and the fundamental values of national and national life. This knowledge is essential to form students who are aware of their role in society. However, the common problems faced are a lack of awareness of the importance of this education, lack of its implementation in everyday life and differences in the thinking, behavior, and morality of each individual. Increasingly modern environmental factors and reliance on technology also affect the lack of social interaction, which impedes the application of character and morality that conforms to customs. Besides, the loss of ethics and decency in everyday life is a complex problem that needs to be addressed. Therefore, efforts are needed to address this problem through Citizenship Education in various educational institutions with the aim of improving the character of students.